To mix, or not to mix?: Mitogenomic insights for risk assessment of an interpopulation translocations of the critically endangered European mink - Jakub Skorupski; Christian Seebass; Wolfgang Festl; Natalia Kiseleva; Przemysław Śmietana; Mihai Marinov (Conservation Science and Practice)
Abstract This study provides a comprehensive, population‐scale analysis of the mitogenome of the critically endangered European mink, Mustela lutreola, involving 52 individuals from Russia, Germany (conservation breeding stock), Romania, and France‐Spain. Significant mitogenomic diversity was identified within the previously presumed genetically homogenous French‐Spanish population, challenging concerns of inbreeding. Despite having lower nucleotide diversity (π = 0.00024) than the German (π = 0.00055) and Russian (π = 0.00048) populations, the French‐Spanish group exhibited impressive haplotype diversity (h = 0.9810) compared to Russian (h = 0.8727) and German (h = 0.7826) populations. Considering genetic diversity and uniqueness, the French‐Spanish population ranked highest in conservation importance, second only to the combined assessment of all other populations. The extensive population structuring identified two distinct haplogroups—the Central‐Eastern European and the Aquitaine‐Navarre—suggesting reconsideration of their conservation status. These findings guide tailored conservation strategies, emphasizing the need for careful interpopulation translocations to protect genetic diversity and prevent outbreeding depression. A decision algorithm for these translocations has been proposed.